Information Retrieval Research at UFMG - Ziviani, Nivio; Gonçalves, Marcos André; de Moura, Edleno Silva; Ribeiro-Neto, Berthier; da Silva, Altigran Soares; Veloso, Adriano (Journal of Information and Data Management, 2011)
This article summarizes Information Retrieval (IR) research conducted at the Universidade Federal de Minas Gerais (UFMG), over more than a quarter of a century. The work of the UFMG IR group has covered some of the key areas in modern IR from crawling, indexing, compression and ranking methods to search engines and recommender systems. Further, its focus on addressing practical problems of relevance to society and on building prototypes to validate the proposed solutions has led to the spin-off of two key start-up companies in Brazil, one of them acquired by Google Inc. to become its R&D center for Latin America.